FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PASIEN KANKER DALAM MENJALANI KEMOTERAPI - Muhammad " Hariyansyah; Sofiana " Nurchayati; Arneliwati " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstarctCompliance is one of the problem occur  tocancer patients that undergoing chemotherapy. Noncompliance affect the success of a treatment. Therapy will not be optimal without the patient's consciousness itself, even lead the treatment failure and be fatal. The purpose of this study was to determine the factors associated with compliance of cancer patients that undergoing chemotherapy.The design used a descriptive correlation with cross sectional approach. Samples were 30 respondents that taken based on inclusion criteria which using accidental sampling technique. The instrument of study was aquestionnaire that designed by the researcher and tested by the validity and reliability.The analysis used univariate and bivariate with Chi-Square test. The results of statistical test by Chi-Square can be concluded that there is no relationship between the understanding of instructions (p value = 0.714), conviction (p value = 0.461)and family support (p value = 1.000) with patient compliance that undergoing chemotherapy. The researcher suggested the family of cancer patients that undergoing chemotherapy to be always faithful to accompany and provide support the patients so they will more obedient to chemotherapy. Keywords: Cancer, Chemotherapy, Conviction